Associação entre o ângulo de fase e o dano muscular induzido pelo exercício físico em atletas de futebol - Almeida Filho, Eder Jackson Bezerra de (2021)
INTRODUCTION: Monitoring Exercise Induced Muscle Damage(EIMD) is necessary to control training loads, however, the tools that assess EIMD are invasive, expensive and/or subjective. Meanwhile, a biophysical marker has been associated with the prognosis of patients with cancer, muscle damage, and improved physical performance. This marker, phase angle(PhA), undergoes modification due to changes in cell membrane integrity that modify the reactance(Xc) of the system. Therefore, it is plausible that PhA is capable of detecting EIMD. OBJECTIVE: To verify if PhA is capable of detecting EIMD in soccer athletes. METHODS: Nine U20 male soccer athletes were spotted in a training session. Before, immediately and 24 hours after training, bioimpedance analysis, blood collection and countermovement jump(CMJ) were performed, in addition to the pain scale before and 24 hours after training. As statistical treatment, the dependent t tests, ANOVA for repeated measures, Pearson and Spearman correlation were performed. RESULTS: Creatine kinase(CK) increased 24h post training (349.67±162.91; 841.67±481.81U/l, p< 0.010), CMJ height immediately reduced (37.64±4.18 ; 33.84±3.74cm; p<0.001) and 24h after training (34.98±3.93cm; p<0.010), the pain increased 24h after training (3.79±2.81; 5.32±2.78cm, p<0.050), the PhA reduced 24h after training compared to immediately after (7.18±0.31; 7.02±0.28, p<0.050) the other biophysical parameters (Resistance and Impedance) did not undergo muted changes. A ∆% AngF and ∆% Xc positive dissipation with variation of the SCM test 24h post training (r=0.827; r=0.743, respectively). CONCLUSION: PhA is able to detect EIMD in soccer athletes.